POLICY OF A SAFE EDUCATIONAL ENVIRONMENT IN SECONDARY EDUCATIONAL INSTITUTIONS: EVALUATION RESULTS (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The article addresses the issue of developing a policy for a safe educational environment in general secondary education institutions based on a comprehensive evaluation of current approaches and practices. The relevance of the study is determined by the growing attention to ensuring safety in educational institutions in the context of social challenges caused by the full-scale war, increasing psychological stress among participants in the educational process, and the need to integrate innovative protection mechanisms and preventive measures. In particular, under modern conditions, education requires not only the formal implementation of safety measures but also their effective integration into everyday practice, which involves the creation of clear regulations, algorithms for action in emergency situations, and the adaptation of international experience.Methods. A set of research methods was used to analyze the features of safety policy formation in secondary education institutions. A survey of social pedagogues was conducted, which made it possible to assess the level of awareness of educators regarding safety issues, particularly physical safety, psychological well-being, communication, and interaction with the community. Comparative analysis methods were used to evaluate the existing practices for ensuring a safe environment in general secondary education institutions in various regions of Ukraine. The systematization and generalization of the obtained data allowed forming a comprehensive understanding of the main challenges facing educational institutions and determining key areas for improving safety policy in education.Results. The study showed that safety policy in schools is at the stage of formation. Most educational institutions implement safety measures, but these measures need improvement in terms of documentation, algorithmization, and regulatory consolidation. There is a lack of clearly defined procedures and action algorithms for real emergency situations, which leads to fragmentation in their implementation.Conclusions. The study confirmed that the formation of a safe educational environment policy is a critically important aspect of education management. Effective safety provision in secondary education institutions requires a comprehensive approach, which includes multi-level interaction between the administration, teaching staff, students, parents, and the local community. Special attention should be given to developing mechanisms for psychological support for participants in the educational process, in particular by integrating psychosocial adaptation programs.Furthermore, the use of innovative technologies, such as video surveillance systems, digital platforms for communication, and algorithmization of processes for responding to potential threats, is important. It is proven that an effective safety policy should be based on regulatory regulation, the adaptation of international experience, and flexible responses to contemporary challenges, which will contribute to the creation of a safe, inclusive, and comfortable educational environment.
Keywords: social pedagogues; socio-pedagogical practices; resource support; safe environment policy; partnership interaction; regulatory framework; communication